ANALYSIS OF INSTITUTIONAL ENGINEERING IN ONE OF THE WET CLIMATE DRY LAND AGROECOSYSTEM VEGETABLE PLANTING - Suharyon, Suharyon; Adri, Adri; Firdaus, Firdaus (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
This study is the first to apply a relationship approach between farmer groups and other supporting institutions to develop a farming system and rice crop institutions in a region. The study aims to solve the problems faced by rice farmers in Rawa Medang village, West Tanjung Jabung Regency, by facilitating the adoption of sustainable rice farming system technology through institutional cooperation. The methodology used in this study applies the Participatory Research Appraisal (PRA) method, to explore the problems faced by rice farmers. Alternative interventions include the formation of several farmer groups or Gapoktan, named Joint Enterprises, a short discussion about the rice farming system, looking at the urgent needs of farmer groups, and connecting them with supporting institutions. Based on the PRA results, the problems prioritized are (1) Rice stem disease by Blas, (2) The presence of snail pests, (3) Seedlings, (4) Capital, (5) Subsidized fertilizer, (6) Meetings between groups, and (7) Technical guidance for rice plants. The novelty of this study is that it introduces a new framework of institutional engineering analysis supporting rice farming technology, based on the FSA (Farming System Analysis) concept. The study also provides empirical evidence of the effectiveness of the relationship approach in improving the productivity and profitability of rice farming in the region. The study contributes to the literature on agricultural development and innovation by highlighting the role of institutional cooperation in enhancing the adoption of sustainable rice farming system technology.